1991
DOI: 10.2739/kurumemedj.38.191
|View full text |Cite
|
Sign up to set email alerts
|

Early Mucosal Gastric Cancer with Extra-Perigastric (n2) Lymph Node Metastasis.

Abstract: a total of 314 cases of early gastric cancer were resected. Of these, 43 (14%) had lymph node metastases, with 6 cases of mucosal (m-) cancer and 37 of submucosal (sm-) cancer. Among the patients with positive lymph node metastases, 37 (86%) had metastases in the Group 1 regional lymph nodes. Eight patients had metastases in the Group 2 lymph nodes, and these involved 2 cases of m-cancer and 6 of sm-cancer. Lymph node metastasis is generally believed to occur in only about 3% of m-cancer, and then mainly in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2001
2001

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Both of these patients had undifferentiated tumors larger than 4.5 cm in diameter. Jumping micrometastasis of lymph nodes shown by CK immunostaining appears to occur more frequently than has been previously reported histologically in m-cancers [21][22][23].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Both of these patients had undifferentiated tumors larger than 4.5 cm in diameter. Jumping micrometastasis of lymph nodes shown by CK immunostaining appears to occur more frequently than has been previously reported histologically in m-cancers [21][22][23].…”
Section: Discussionmentioning
confidence: 51%
“…Lymph node metastasis has been observed mainly in perigastric nodes in m-and submucosal (sm)-cancers, although jumping metastases to extra-perigastric lymph nodes have been reported histologically in early gastric cancer [17,21]. In our study, two patients showed micrometastasis in the group 3 lymph nodes, but not in any of the group 1 or 2 lymph nodes.…”
Section: Discussionmentioning
confidence: 66%